Utilization of seismic refraction data for the study of structure of Bang hot-water source, Le Thuy, Quang Binh - Vu*, Tran Anh; Toan, Dinh Van; Tuyen, Doan Van; Phong, Lai Hop; Ninh, Duong Thi; Quang, Nguyen Thi Hong; Dat, Pham Ngoc (Vietnam Journal of Earth Sciences, 2016)
Study of the geological structural elements in the area of geothermal sources is important for identifying the geothermal reservoir, the object is capable of energy production. This paper presents the preliminary results of the structural study obtained by the seismic refraction data in the area of hot water spring Bang, Le Thuy, Quang Binh. The exploration was carried out in 2014 by using 150 wireless Texan instruments produced by Refraction Technology Company - USA and provided by the Institute of Earth Sciences, Academia Sinica, Taiwan. The data were collected from 4 profiles, cutting several tectonic faults around the exposed hot water source. The seismic signals were strong on the records of each instrument, especially the signals of refraction wave. The 2D seismic tomographic technique is applied for data interpretation to create the velocity structural models from 4 observation profiles. Based on the velocity structures, the area can be separated into three main structural layers, characterized generally by three velocity ranges: 3,0 – 4,1 km/s; 4,2 – 5,1 km/s and 5,2 – 6,1 km/s, respectively. The block separation by the faults of different size with the subsidence tendency from southwest to the northeast parts of the region is apparently reflected in the seismic data obtained in this study. The narrow lower velocity vertical structure detected inside the southern well-consolidated rock uplifted block away from the exposed hot water source more than 2 km, under the sub meridian extension Quaternary structure probably related to the breaking up of the bedrocks caused by the tectonic activity in the region. Perhaps, the object played a role as the thermal fluid channel in the geological history time and is closely related to the geothermal reservoir predicted recently by magnetotelluric investigations in this location. References Berrynam J. G., 1991, Lecture Notes on nonlinear inversion and tomography. Earth Resources Laboratory, Massachusetts Institute of Technology, USA, pp. 164. Ester Z., Darko V., 2010, A careful blasting technique during construction of underground opening for nuclear waste repository. Pub. of University 0f Zagreb, Croatia, https://www.iaea.org.inis/collectionStore/public/29/064/29064418.pdf, 384-390. Flynn T., Quy H. H., 1997. Assessment of the geothermal resources of Socialist Republic of Vietnam. Geothermal resources Council Transactions, vol.21, 341-345. Hoang Huu Quy, 1998. Overview of the Geothermal potential of Vietnam. Geothermics, Vol.27, n.1, 109-115. Honjas W., Pullammanappallil S. K., Lettis W. R., Plank G. L., Louie J. N., and Dchweichert R., 1997, Predicting subsurface structure within the Dixie Valley geothermal field, Dixie Valley, Nevada, using a non-linear optimization scheme: Geothermal Resource Council Bullentin, v. 26, p. 45-52. Pullammanappallil S. K., and Louie J. N., 1994, Generalized simulated-annealing optimization for inversion of first arrival times. Bullentin of the seismological society of America, v. 84, p. 1397-1409. Harder Steven, Van Toan Dinh, 2011. Collecting Deep Seismic Data in Densely Populated Vietnam. EOS, Transaction; American Geophysical Union, Vol. 92, No 3, 21-22. Thorne Lay, Terry C. Wallace, 1995. Modern global Seismology. Academic Press. Inc., San Diego, California 521 pp. Mai Thanh Tan, 2011. Seismic Prospecting. Transportation publishing house, Hanoi, 524 pages ( in Vietnamese). Tesarik D. R., W. A. Hustrulid, and U. Nyberg, 2010, Assessment and application of a single-charge blast test at the Kurina mine, Sweden, https://www.cdc.gov.hiosh/minning/userfiles/works/aaaoa.pdf. Dinh van Toan, Steven Harder, Pham Nang Vu, Trinh Viet Bac, Doan Van Tuyen, Lai Hop Phong, Tran Anh Vu, Nguyen Thi Hong Quang, 2008. The first deep seismic investigations in North Vietnam. Vietnam J. of Geology, series B, N31-32, 213, 219. Dinh Van Toan, Steven Harder, 2008, Near-vertical Moho reflections under hanoi Basin, Vietnam. EOS Trans. 89(53), AGU Fall meetting Suplementabstract S13D-03. Dinh Van Toan ( project manager), et al., 2010. Study on deep crustal structures of Northern Vietnam with the purpose to obtain a more confidence in the geological hazard prediction by using deep seismic and magnetotelluric investigations. Final report of National project ( Code KC.08.16/11-15), 228 pages, Hanoi, Institute of Geological Sciences. Dinh van Toan, Steven Harder, Trinh Viet Bac, Doan Van Tuyen, Lai Hop Phong, Tran Anh Vu, Nguyen Thi Hong Quang,2011. Study on the Earth crustal structure by the seismic refraction data collected along two profiles in Northern Vietnam. Vietnam Journal of earth Sciences, Vol.33, No.3, 538–548. Tran Van Tri ( Project manager), et al., 2004. Map of geology and mineral resources of Vietnam on scale 1:1,000,000. Publication of the Department og Geology and mineral recources of Vietnam, Hanoi ( in Vietnamese). Doan Van Tuyen, Dinh Van Toan, Trinh Viet Bac, 2008. The sudy of geothermal resources to develop clean energy in Vietnam. Vietnam Journal of Earth Sciences, 30(2), 153-160. Doan Van Tuyen, Tran Anh Vu, Lai Hop Phong, Le Van Si, Pham Ngoc Dat, Duong Thi Ninh, Dinh Van Toan, Nguyen Thi Hong Quang, 2015. Results of magneto-telluric survey for studying geothermal system in area Bang - Quang Binh province Vietnam Journal of Earth Sciences 37(1), 48-56. Doan Van Tuyen, Tran Anh Vu, Lai Hop Phong, Dinh Van Toan, Le Van Si, 2015. Structural Features of Geothermal Field from Magnetotelluric Survey in Northern Central Region of Vietnam. Proceedings of World Geothermal Congress 2015, Melbourne, Australia, 1-25 April 2015, Online- https://pangea.stanford.edu/ERE/db/WGC/2015. Doan Van Tuyen ( project manager),et al. 2016. A study of the potential geothermal recources for energy development in Vietnam. National project ( Code KC.08.16/11-15), final report, 228 pages, Hanoi, Institute of Geological Sciences ( in Vietnamese). Reynods J. M., 2011, An introduction to applied and environmental geophysics. John Wiley & Son, Ltd., Chichester, 2nd ed., 712 pp. Udias Agustin, 1999. Principles of Seismology.Cambridge University Press, 475 pp. Uruh J. R., Pullammanappallil S. K., and Honjas W., 2001. New seismic imaging of the geothermal field, eastern California: Proceedings of the 26th workshop on Geothermal Reservoir Engineering, Standford University, CA, January 29–30. White D. J., 1989. Two dimentional seismic refraction tomography. Geophys. J. Int., 97, 223-245. Zelt Colin A., 1999. Modelling strategies and model assessment for wide-angle seismic travaltime data. Geophys. J. Int., 139, 183-204.